(untitled) (Research, Society and Development, 2022)
COVID-19 is still a new disease, involved in the pandemic that has been plaguing us since 2020. It has 4 stages: 1°) Upper respiratory tract infection with fever, muscle fatigue and pain; 2°) Dyspnea and pneumonia; 3rd) Hyperinflammatory clinical picture-cytokine storm and 4th) Outcome due to death or recovery of the patient, with possible sequelae in his recovery. In the Northeast region, there are states with a very low Human Development Index (HDI), where diseases prevail and succumb to undesirable outcomes. Thus, the objective of this study was to trace the epidemiological profile of hospitalizations and deaths by COVID-19 in the Northeast, in the year 2020. An epidemiological, descriptive, time series study was carried out, with secondary data from the SUS-DATASUS Information System, that were tabulated in an EXCEL spreadsheet and exported to Bioestat 5.3 for statistical analysis. The results showed a predominance of hospitalizations in: Pernambuco (21.58%), Ceará (20.33%) and Bahia (19.45%); male-had 53.53% of notifications and female-44.33%; brown race/color - most registered (54%); schooling-predominance of non-completion (40.67%); age group - over 60 years old (55.83%); proportions of deaths from hospitalizations: Maranhão (45.8%), Ceará (40.2%) and Alagoas (39.1%). The high number of deaths in hospitalizations due to COVID-19 in 2020 reinforces that more efficient public policy management is essential, with coordination, consistent theoretical basis, resource management, action in preventive measures and improvement in treatment, which includes improvement of measures. taken during hospitalization, aiming to reduce this frightening percentage of deaths due to hospitalizations.